Thyrotoxic periodic paralysis. A case report - G. R. Ramazanov; E. V. Shevchenko; L. Kh.-B. Akhmatkhanova; S. S. Petrikov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2022)
In 19-26% of patients hospitalized with suspected stroke, the cause of neurological symptoms are not cerebrovascular diseases. In this case of newly diagnosed thyrotoxic periodic paralysis we presented the clinical, laboratory and instrumental features of the disease. The search for the cause of periodic paralysis allowed to identify an endocrinological disease - diffuse toxic goiter, prescribe antithyroid therapy. The data of prospective patient observation are presented. We discussed a differential diagnostic range of diseases with acute low paraparesis, including rupture of an aneurysm of the anterior communicating artery, bilateral infarction in territory of anterior cerebral arteries, thrombosis of upper sagittal sinus, acute spinal strokes and Guillain - Barre syndrome. The need to include thyrotoxic periodic paralysis in patients with acute lower paraparesis in the differential diagnostic series is substantiated.